CAMPUR KODE DAN ALIH KODE PEMAKAIAN BAHASA BALI DALAM DHARMA WACANA IDA PEDANDA GEDE MADE GUNUNG - Ratmika, Ni Ketut Ayu (Humanis; Volume 5. No. 3. Desember 2013, 2013)
Research on code mixing and code switching over the Bali language in dharma wacana Ida Pedanda Gede Made Gunung in general aims to analyze and solve problems on sociolinguistics aspects that are considered to be a confusion in the community. At the level of data preparation techniques used method listen completely to tap the bottom, followed by technique and method talk listen completely involved with interview. The level of analysis used data matching methods and matching ekstralingual intralingual contact technique is compared with the case of tree equalize. Presentation of the data analysis method used informally assisted with deductive and induktive techniques. Result obtained in this research kinds of code mixing is word, phrases, and clause. Kinds of code mixing pursuant to coming from absorption that is inner code mixing, outer code mixing, and hbryd code mixing. Kinds of code switching pursuant to switchover of its language that is inner code switching and outer code switching. Factor in the causes of the code mixing in dharma wacana grounded by three factors is namely speakers of factor, factor language media, and the prestige factor (authority). Factor over the cause of the code switching grounded by four factors is namely speaker participant factor, factor of language, situation factor, and factor topic.
Keywords: sociolinguistics, code, language